A new technique of autologous bone grafting for open-wedge high tibial osteotomy - Gong, Yongchao; Jin, Lin; Wang, Yanwei; Liu, Boxu; Shen, Pengfei; Zhang, Zhiang; Yuwen, Peizhi; Zhao, Kuo; Ma, Lijie; Chen, Wei; Zhang, Yingze (Frontiers in Surgery, 2024)
This study aimed to demonstrate the application of orthotopic bone flap transplantation with a fibula transplantation (OBFT-FT) in open-wedge high tibial osteotomy (OW-HTO) and to assess the effect of OBFT-FT on gap healing.From January to July 2020, 18 patients underwent OWHTO with OBFT-FT were reviewed in this study. Demographics, postoperative complications, radiological and clinical outcomes of patients were collected. Finally, clinical outcomes of patients were analyzed.Results: A total of 14 patients were included in this study. The average age and body mass index (BMI) were 59.6 ± 9.2 years and 28.1±4.5kg/m 2 . The average correction angle and gap width were 9.5 ± 1.8°and 10.2±2.7mm. The rates of radiological gap healing at 6th week, 3th month, and 6month were 42.9%, 85.7%, 100%, respectively. The mean Lysholm Score, IKDC Score, and VAS scores at 6th month follow-up were significantly better than those at preoperative (p<0.001, p<0.001, p=0.001 respectively). And, none delayed union or nonunion, collapse, loss of correction and surgical site infection were found.As a new technique for autologous bone graft, the OBFT-FT could be successfully applied in the treatment of gap healing after OWHTO, and excellent radiological and clinical outcomes cloud be seen in patients' short-term follow-up.